PENGUJIAN EMPIRIS BAGAIMANA KUALITAS SISTEM INFORMASI AKUNTANSI YANG DIPENGARUHI OLEH ETIKA ORGANISASI BERIMPLIKASI TERHADAP KUALITAS INFORMASI AKUNTANSI - Lesi Hertati; Azhar Susanto; Wahyudin Zarkasyi; Harry Suharman; Haryono Umar (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2019)
Accounting Information System is one of the most important parts in an organization. Function Organizational ethics is very influential on accounting information systems will produce accounting information needed by managers and non-managers of an organization as a basis for the decision making process in carrying out its functions or duties. The functions and tasks of managers or non-managers of related units within an organization vary greatly depending on the type of organization, the sections and levels that exist within the organization. The functions and tasks of managers or non-managers differ because the different levels and sections that cause the information needs of managers and non-managers are to support different functions and tasks. The difference in information requirements will lead to different data that must be entered and the accounting information system format used. Reality states that many accounting information systems in various state-owned enterprises have a variety of problems including problems of integration, ease of use, ease of access, ease of adaptation to changing conditions and the ability to produce accounting information as needed. The purpose of this study was to determine how much influence the organization's ethics has on the quality of accounting information systems and their implications for the quality of management accounting information. This method is descriptive and verification method, and the analysis tool is SEM Lisrel modeling. The results showed that user ethics significantly influence the quality of accounting information systems and their implications for the quality of accounting information.